COPING WITH THE “NIMBY SYNDROME”: POLITICAL ISSUES RELATED TO THE BUILDING OF BIG INFRASTRUCTURES IN LIBERAL DEMOCRACY COUNTRIES - Agostino MASSA (Security and Defence Quarterly, 2019)
The location and building of big hazardous infrastructures is a typical feature of the modernization process, in all countries and epochs. Since they are usually useful for a large region but their impact is very localized, the people living around the places where these facilities are active, or where their building is planned, very often organize and perform protest activities against them.